Characteristics of place and the rural disadvantage in deaths from highly preventable causes. (January 2020) - Roth, Adam R.; Denney, Justin T.; Amiri, Solmaz; Amram, Ofer
Abstract: Extensive research has documented higher mortality in rural parts of the United States compared to urban areas. Much of this work focuses on aggregate rates, documenting a rural mortality penalty that has been increasing over the last three decades. Advances in place-based analyses suggest the importance of community resources for individual mortality but have largely focused on urban spaces. We advance knowledge on rural-urban mortality disparities by focusing on differences for highly preventable causes of death. Using unique geocoded mortality records from Washington state, we match individual-level attributes with area-level measures of socioeconomic conditions to examine whether characteristics of place elucidate the rural mortality penalty. We find that rural decedents have greater odds of dying from highly preventable causes compared to their urban counterparts. Place-based socioeconomic measures, meanwhile, independently associate with the odds of dying from highly preventable causes. However, we find no evidence that the relationship between socioeconomic conditions and highly preventable death varies across geographic contexts. Highlights: Rural adults are more likely to die from the most highly preventable causes (HPC). Place-level socioeconomic advantage negatively associates with HPC. Policies to improve socioeconomic conditions will decrease mortality disparities.